Advanced tarnish-resistant silver alloys using Cu, Al, Zn, and Be: composition optimization and surface passivation - Harsha Kozhakkattil; Mukaddar Sk; Ranjit Thapa; G.S. VinodKumar (Applied Surface Science Advances, 2025)
A novel class of tarnish-resistant silver alloys containing Cu, Al, Zn, and Be was developed. While Cu is a conventional alloying element in sterling silver (Ag-7.5 wt. %Cu), the addition of Al, Zn, and Be was aimed at forming stable surface oxides to inhibit Ag₂S formation that tarnishes silver alloy surface. The silver alloys produced were subjected to Passivation Heat Treatment (PHT) under oxygen atmosphere, promoting the formation of protective oxide layers. The XRD, SEM/EDX, and XPS characterization confirmed the formation of oxides contributing to tarnish resistance. Accelerated tarnish tests and UV–Visible reflectance spectroscopy demonstrated that Ag-3.5Cu-2Zn-1.9Al-0.1Be alloy exhibited strong resistance to tarnishing, having maximum reflectance values in the range of 60–70 %. The trace addition of Be was pivotal in controlling oxidation by creating a barrier for the diffusion of oxygen during PHT, preventing CuO related fire stains and ensuring tarnish resistance. The adsorption energy ratios of sulphur and oxygen of the silver alloys were studied computationally. The lower value of the ratio is implicative of a preference for oxidation over sulphidation. The value obtained is 0.373 for Ag-3.5Cu-2Zn-1.9Al-0.1Be, which is the least, and it is due to the presence of appropriate amounts of Zn, Al, and Be in the composition.